Reaction of different cell types of the brain on neurotoxin cuprizone and hormone melatonin treatment in young and aging mice - Labunets, Irina; Rodnichenko, Anzhela; Savosko, Sergey; Pivneva, Tetyana (Frontiers in Cellular Neuroscience, 2023)
ABSTRACT Purposes: (1) to evaluate changes of the brain macrophages, astrocytes, T-cells, neural stem cells, neurons and CNS functioning in the neurotoxin cuprizone-treated mice of different age; and (2) to assess in such mice the effects of exogenous melatonin and possible courses of its action. Results: The numbers of the GFAP+-, CD3+-, CD3+CD4+, CD3+CD8+, CD11b+, CD3+CD11b+, Nestin+-cells and macrophages phagocytic latex and MDA content were increased in the brain of young and aging mice under cuprizone influenceю In both age groups of mice the proportion of unchanged neurons in the brain, motor, emotional and research activities, and muscle tone were decreased. Regardless of the age of the mice, administration of melatonin resulted in a decrease of the number of GFAP+-, СD3+- cells and their subpopulations, activated macrophages, and malondialdegide content. In such mice, the proportion of brain unchanged neurons increased as the number of Nestin+-cells decreased. The behavioral responses were also improved. Besides, the number of bone-marrow GM-CFC and the blood level of monocytes and thymulin increased. The effects of both neurotoxin and melatonin on the brain astrocytes, macrophages T-cells and immune system organs as well as the structure and functioning of neurons were more pronounced in the young mice. Conclusions. We have observed the involvement of the astrocytes, macrophages, T-cells, neural stem cells and neurons in the brain reaction of mice different age after administration of neurotoxine cuprizone and melatonin. The brain cell composition reaction has the age features. The neuroprotective effects of melatonin in cuprizone-treated mice have been realized through an improvement of the brain cell composition and oxidative stress factors and functioning of bone marrow and thymus.